Nilai Perusahaan Infrastruktur: Peran Profitabilitas, Likuiditas, dan Struktur Modal - Ni Kadek Dewi Octaviani; I Gusti Ayu Ratih Permata Dewi; Ni Luh Putu Ratna Wahyu Lestari (Juara: Jurnal Riset Akuntansi, 2026)
In recent years, the challenges faced by corporate entities in the infrastructure sector related to domestic and global conditions have escalated. Post-pandemic economic dynamics have become a primary concern, driven by exchange rate volatility and adjustments in government regulations that have implications for stock prices. Corporate entities in the infrastructure sector play a crucial role in accelerating national development and providing public services, both of which contribute to national economic growth. Along with rapid technological advancements, infrastructure companies are required to optimize internal operational effectiveness and service quality. This study aims to analyze the effect of profitability, liquidity, and capital structure on firm value in infrastructure sector companies listed on the Indonesia Stock Exchange (IDX) during 2021-2024. This research employs a quantitative approach using panel data regression analysis. The sampling technique uses purposive sampling, resulting in 49 companies as the research sample. The data used is secondary data obtained from annual financial reports and analyzed using EViews 12. The results indicate that profitability has a negative effect on firm value, while capital structure and liquidity have no significant effect on firm value.